Pemodelan matematika dalam epidemiologi: Analisis dinamika dan penyebaran penyakit menular - Putri, Naura Deviyanti Nivia (Maliki Interdisciplinary Journal, 2024)
This abstract provides an overview of the use of mathematical models in understanding the dynamics of infectious disease spread. The article discusses the basic SIR (Susceptible-Infectious-Recovered) model and its variations, outlining theoretical foundations and applications to several well-known epidemics. Mathematical approaches are used to predict and control disease spread, offering valuable insights for public health planning. The study also includes the use of computer simulations and empirical data for model validation.